Invasive species differ in key functional traits from native and non‐invasive alien plant species. (19th July 2019) - Mathakutha, Rabia; Steyn, Christien; le Roux, Peter C.; Blom, Izak J.; Chown, Steven L.; Daru, Barnabas H.; Ripley, Brad S.; Louw, Anche; Greve, Michelle
Abstract: Questions: Invasive species establish either by possessing traits, or trait trade‐offs similar to native species, suggesting pre‐adaptation to local conditions; or by having a different suite of traits and trait trade‐offs, which allow them to occupy unfilled niches. The trait differences between invasives and non‐invasives can inform on which traits confer invasibility. Here, we ask: (a) are invasive species functionally different or similar to native species? (b) which traits of invasives differ from traits of non‐invasive aliens and thus confer invasibility? and (c) do results from the sub‐Antarctic region, where this study was conducted, differ from findings from other regions? Location: Sub‐Antarctic Marion Island. Methods: We measured 13 traits of all terrestrial native, invasive and non‐invasive alien plant species. Using principal components analysis and phylogenetic generalized least‐squares models, we tested for differences in traits between invasive (widespread alien species) and native species. Bivariate trait relationships between invasive and native species were compared using standardized major axis regressions to test for differences in trait trade‐offs between the two groups. Second, using the same methods, we compared the traits of invasive species to non‐invasive aliens (alien species that have not spread). Results: Between invasive and native species, most traits differed, suggesting that the success of invasive species is mediated by being functionally different to native species. Additionally, most bivariate trait relationships differed either in terms of their y ‐intercept or their position on the axes, highlighting that plants are positioned differently along a spectrum of shared trait trade‐offs. Compared to non‐invasive aliens, invasive species had lower plant height, smaller leaf area, lower frost tolerance, and higher specific leaf area, suggesting that these traits are associated with invasiveness. The findings for the sub‐Antarctic corresponded to those of other regions, except lower plant height which provides a competitive advantage to invaders in the windy sub‐Antarctic context. Conclusion: Our findings support the expectation that trait complexes of invasive species are predominantly different to those of coexisting native species, and that high resource acquisition and low defence investment are characteristic of invasive plant species. Abstract : This study, conducted in the remote sub‐Antarctic environment, shows that the trait complexes of invasive species are predominantly different to those of coexisting native species, indicating that invasive species fill different niches to native species; and that high resource acquisition and low defence investment are characteristic of invasive plant species.